Inquérito sorológico das infecções por Babesia bovis (Babes, 1888), Babesia bigemina (Smith e Kilborne, 1893) e Anaplasma marginale (Theiler, 1910) em bovinos no Estado de Alagoas, Brasil - PORTO, Wagnner José Nascimento (2007)
The prevalence of serum antibodies to Babesia bovis, Babesia bigemina and Anaplasma marginale infections were investigated in cattle farming herds from three regions called Sertão, Agreste and Leste of Alagoas State, Brazil. Sera samples from 1,155 cattle raised in 26 farms were evaluated by enzyme immunoassay (indirect ELISA). At the same time a questionnaire survey was conducted in the data were also analyzed. According to the results, 70.22% (811/1155) of the animals were positive for B. Bovis and 77.40% (894/1155) for B. bigemina and 27.45% (317/1155) of the animals were positive for antibodies against A. marginale The seroprevalence showed that the State of Alagoas is considered enzootically unstable for B. bovis and A. marginale enzootically stable for B. bigemina. The prevalence of Babesia sp infection was higher (p<0.05) in beef cattle than for dairy cattle and mixed herds. Regarding the infection by A. marginale, antibodies levels were more elevated in dairy cattle than others kind of rearing, but this difference was not significant. It is concluded that preventive measures should be adopted especially unstable areas.